2013
DOI: 10.1093/schbul/sbt094
|View full text |Cite
|
Sign up to set email alerts
|

Appraisals and Responses to Experimental Symptom Analogues in Clinical and Nonclinical Individuals With Psychotic Experiences

Abstract: The findings are consistent with cognitive models of psychosis, with maladaptive appraisals and response styles characterizing the C group only. Clinical applications of both tasks are suggested to facilitate the identification and modification of maladaptive appraisals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 35 publications
6
60
0
Order By: Relevance
“…Alterations in appraisals have been found in people with schizophrenia (Garety et al, 2013;Peters et al, 2012) and in clinical and non-clinical individuals with psychotic experiences (Ward et al, 2014). It has been suggested that intervention approaches might focus on enhancing protective factors and resilience in coping with the consequences of social adversities(Gayer-Anderson and Morgan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in appraisals have been found in people with schizophrenia (Garety et al, 2013;Peters et al, 2012) and in clinical and non-clinical individuals with psychotic experiences (Ward et al, 2014). It has been suggested that intervention approaches might focus on enhancing protective factors and resilience in coping with the consequences of social adversities(Gayer-Anderson and Morgan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The idea is that these adaptive responses manifest themselves as positive symptoms as a result of cognitive schema and appraisal-processes which are imposed on abnormal sensory processes through top-down mechanisms [88,91,92].…”
Section: Neural Oscillations Coordination Dynamics and The Search Fomentioning
confidence: 99%
“…Maladaptive appraisals endorsed by patients typically represent perceptions of externalised, personalised threat [6][7][8]. Attentional and interpretative cognitive biases are considered to underlie these threat-based appraisals [2].…”
Section: Introductionmentioning
confidence: 99%